KEPATUHAN DAN KEPUASAN TERAPI DENGAN ANTIDIABETIK ORAL PADA PASIEN DIABETES MELITUS TIPE 2 RAWAT JALAN DI RSUP Dr. SARDJITO YOGYAKARTA - , RAIMUNDUS CHALIKS, Dr. Tri Murti Andayani, Sp.FRS, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Management of type 2 diabetes mellitus may provide optimal results with an awareness of individual behavior such as adherence to treatment. The objective of this study was to assess oral hypoglycemic medication adherence (OHA) and its association with treatment satisfaction. In addition, it also determines the influence of intrapersonal and disease characteristics and treatment factors to adherence. Diabetes Medication This is a cross sectional study which was carried out with sample of 101 patients with type 2 diabetes mellitus in outpatient clinic of Endocrinology of Dr. Sardjito Hospital, Yogyakarta, during February 2012 to April 2012. The 8-item Morisky Medication Adherence scale (MMAS-8) and Satisfaction Tool Scale (DMSAT) were used to assess adherence and treatment satisfaction, respectively. The main outcome measure was level of adherence, treatment satisfaction and the relationship between adherence and treatment satisfaction among patients with type 2 diabetes. Statistical analysis using SPSS. The results of the study was found that 62.4% of patients were adherent to treatment. The mean score of overall satisfaction is satisfied category (7.15±1.7). Mean satisfaction with respect to well-being, medical control, lifestyle, and convenience domain were 6.64 ± 1.54, 7.08 ± 1.40, 7.06 ± 1.21, and 7.79 ± 0.94, respectively. Adherence was significantly relationship with treatment satisfaction (p = 0,045) and HbA1c (p = 0,001). Significant relationship was found between HbA1c and treatment satisfaction (p = 0,011). Intrapersonal and Disease characteristics and treatment factors was not significantly contribute to adherence. The results support that patients with higher level of satisfaction show the achievement of better clinical outcomes (HbA1c <7%)